Census of the population 1920 - Occupational groups - Brantgärde, Lennart (University of Gothenburg, 1991)
This data collection contains information about total population, total number of professionally employed, income and property within the principal occupational groups agriculture and subsidiary industry, industry and craft, commerce, transport, storage and communication, public service, domestic work, and former professionally employed, and also within subgroups of these principal groups.

This data collection contains information about total population, total number of professionally employed, income and property within the principal occupational groups agriculture and subsidiary industry, industry and craft, commerce, transport, storage and communication, public service, domestic work, and former professionally employed, and also within subgroups of these principal groups.
Folkräkningen 1920 - Yrkesgrupper
Keywords: occupations; yrken; population; befolkning; census data; folkräkningsdata; rural population; landsbygdsbefolkning; urban population; stadsbefolkning; Censuses; Folkräkningar; Employment; Sysselsättning; HISTORY; HISTORIA; History; Historia